The impact of perceived similarity on tacit coordination: propensity for matching and aversion to decoupling choices - Chierchia, Gabriele; Coricelli, Giorgio (Frontiers in Behavioral Neuroscience, 2015)
Homophily, or “love for similar others”, has been shown to play a fundamental role in the formation of interpersonal ties and social networks. Yet no study has investigated whether perceived similarities can affect tacit coordination. We had 68 participants attempt to maximize real monetary earnings by choosing between a safe but low paying option (that could be obtained with certainty) and a potentially higher paying but “risky” one, which depended on the choice of a matched counterpart. While making their choices participants were mutually informed of whether their counterparts similarly or dissimilarly identified with 3 person-descriptive words as themselves. We found that similarity increased the rate of “risky” choices only when the game required counterparts to match their choices (stag hunt games). Conversely, similarity led to decreased risk rates when they were to tacitly decouple their choices (entry games). Notably, though similarity increased coordination in the matching environment, it did not did not increase it in the decoupling game. In spite of this, similarity increased (expected) payoffs across both coordination environments. This could shed light on why homophily is so successful as a social attractor. Finally, this propensity for matching and aversion to decoupling choices was not observed when participants “liked” their counterparts but were dissimilar to them. We thus conclude that the impact of similarity of coordination should not be reduced to “liking” others (i.e. social preferences) but it is also about predicting them.